Chitosan scaffold modified with D-(+) raffinose and enriched with thiol-modified gelatin for improved osteoblast adhesion. (2nd February 2016) - Galli, C; Parisi, L; Elviri, L; Bianchera, A; Smerieri, A; Lagonegro, P; Lumetti, S; Manfredi, E; Bettini, R; Macaluso, G M
Abstract: The aim of the present study was to investigate whether chitosan-based scaffolds modified with D-(+) raffinose and enriched with thiol-modified gelatin could selectively improve osteoblast adhesion and proliferation. 2, 3 and 4.5% chitosan films were prepared. Chitosan suitability for tissue engineering was confirmed by protein adsorption assay. Scaffolds were incubated with a 2.5 mg ml −1 BSA solution and the decrease of protein content in the supernatants was measured by spectrophotometry. Chitosan films were then enriched with thiol-modified gelatin and their ability to bind BSA was also measured. Then, 2% chitosan discs with or without thiol-modified gelatin were used as culture substrates for MC3T3-E1 cells. After 72 h cells were stained with trypan blue or with calcein AM and propidium iodide for morphology, viability and proliferation assays. Moreover, cell viability was measured at 48, 72, 96 and 168 h to obtain a growth curve. Chitosan films efficiently bound and retained BSA proportionally to the concentration of chitosan discs. The amount of protein retained was higher on chitosan enriched with thiol-modified gelatin. Moreover, chitosan discs allowed the adhesion and the viability of cells, but inhibited their proliferation. The functionalization of chitosan with thiol-modified gelatin enhanced cell spreading and proliferation. Our data confirm that chitosan is a suitable material for tissue engineering. Moreover, our data show that the enrichment of chitosan with thiol-modified gelatin enhances its biological properties.